Pazopanib-associated remodeling of platelet-immune cell crosstalk and immune suppressive platelet-derived extracellular vesicles in metastatic RCC - Lupoli, Gianpiero; Bergamini, Stefano; Salsetta, Jeannette; Mereu, Alessandro; Cova, Agata; D’Angelo, Elisa; Shahaj, Eriomina; Vergani, Elisabetta; Stroscia, Martina; Di Carlo, Emma; Rivoltini, Licia; Verzoni, Elena; et al. (Frontiers in Immunology, 2026)
BackgroundAntiangiogenics promote immune activation by reducing myeloid-derived suppressor cells (MDSCs) and enhancing natural killer (NK) and T cell functions in metastatic RCC patients. However, these effects are transient, leading to compensatory immunosuppression. Platelets (PLT) and their extracellular vesicles (PLT-EVs) modulate immune and angiogenic pathways, suggesting a role in immune reprogramming during therapy.MethodsCirculating EVs were longitudinally profiled in metastatic RCC patients (n=8) undergoing Pazopanib therapy. EVs, isolated by differential ultracentrifugation from baseline, 3- and 6-month plasma samples, were characterized by bead-based multiplex assay and nanoparticle tracking analysis. Results were correlated with blood counts, RNA-seq and flow cytometry immune profiles.ResultsPazopanib induced temporally structured EV compartment alterations. After three months, EVs were enriched in immune markers (CD8, CD56, CD19, CD1c, HLA-DR), consistent with immune activation, whereas PLT-derived markers (CD41b, CD42a, CD29) were diminished. By six months, PLT-EV markers recovered, with CD62P+ and CD29+ EVs co-expressing immunoregulatory and angiogenic molecules (CD209, CD105). PLT-EV abundance correlated with the expansion of regulatory T cells (Tregs), PD-L1+ monocytes and MDSCs, together with suppression of NK cells. PLT activation and PDGF signaling pathways decreased in PBMC from patients with clinical benefit.ConclusionsDespite the small sample size and absence of functional experiments, our results suggest that Pazopanib promotes cytotoxic immune programs but, by six months, reprograms PLT-EVs towards different adhesion characteristics contributing to Treg and MDSC expansion while suppressing NK activity. PLT-EVs may influence the balance between immune activation and suppression during anti-angiogenic therapy, suggesting PLT-EVs as biomarkers and therapeutic targets in mRCC.